PERTANGGUNGJAWABAN PENGGUNA ANGGARAN TERHADAP TINDAK PIDANA KORUPSI DANA BANTUAN SOSIAL (STUDI PUTUSAN MA.NO. 995 K/PID.SUS/2017) - Sukino Sukino (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
The rule of law regarding the accountability of corruption is regulated in Law Number 31 Year 1999 in conjunction with Law Number 20 Year 2001. In the formulation of the law the corruption has undergone substantial changes. In the 1999 Corruption Law, it regulated criminal penalties such as capital punishment, regulating specific minimum criminal threats, regulating the threat of higher fines, and on the other hand expanding actions including criminal acts of corruption. Thus, the change in sanctions like that at least psychologically can make Corruptors afraid or give a deterrent effect to the public so they do not commit corruption.